[OP.3A.01] GLOMERULAR HYPERFILTRATION. A PREDICTOR OF ADVERSE CARDIOVASCULAR OUTCOME. (September 2017) - Reboldi, G.; Verdecchia, P.; Beilin, L.; Casiglia, E.; Eguchi, K.; Imai, Y.; Kario, K.; Ohkubo, T.; Pierdomenico, S.; Schwartz, J.; Wing, L.; Palatini, P.
Abstract : Objective: The prognostic role of low estimated glomerular filtration rate (eGFR) is well established. In contrast, the association between greater than normal eGFR, i.e. glomerular hyperfiltration (GH), and cardiovascular events (CVE) is much less characterized. The present study was conducted to test the hypothesis that GH is independently associated with risk of adverse cardiovascular outcome in a large multiethnic population. Design and method: The analysis was performed in 8824 participants (55% men) aged 52 ± 16 years enrolled in 8 prospective studies in Australia, Italy, Japan, and U.S.A.. Using the 5th and 95th percentiles of the age and sex specific quintiles of CKD-EPI-calculated eGFR, we identified 3 groups: low (LF), high (HF) and normal (NF) eGFR. The unadjusted relationship between eGFR categories and time to CVE occurrence was estimated using Kaplan-Meier product-limit method and compared by the Mantel (log-rank) test. We then tested the independent prognostic role of eGFR categories using study-stratified multivariable Cox models. Results: The median (IQR) eGFR were: 48.2 (38.1, 58.7), 81.4 (69.6, 95.8) and 111.2 (99.1, 126.7) ml/min/1.73m 2 for LF, NF, and HF participants, respectively (p < 0.001). Compared with LF and NF, HF (N = 426) were younger, mostly male and of white race (p < 0.001). During a median follow-up of 5.7 years there were 722 CVE. Crude event rates were higher for both HF (1.8 per 100-p-years) and LF (2.1 per 100-p-years) as compared with NF (1.2 per 100-p-years) (p < 0.001). In unadjusted survival analyses the cumulative incidence of CVE was similar in HF and LF and higher than in NF (log-rank p < 0.001). In Cox models including age, sex, average 24-hour BP, smoking, diabetes, and cholesterol, both HF (HR 1.5, 95% CI, 1.2–2.1, p < 0.001) and LF (HR 2.0, 95% CI, 1.5–2.6, p < 0.001) participants had a higher risk of CVE as compared to NF. Inclusion of night-time BP dipping in the regressions did not change the strength of the associations. Conclusions: These data show that GH is a strong and independent predictor of CVE in a large multiethnic population. Our findings support a U-shaped relationship between eGFR categories and adverse cardiovascular outcome.